Pengaruh Puasa Menurut Perspektif Islam Dan Sains Dalam Menurunkan Berat Badan Pada Pasien Obesitas Dan Diebetes - Maulida, Khalisha Luthfia; Pratiwi, Martini Cahaya; Qolbi, Nadya Syifa (Journal of Creative Student Research, 2023)
Fasting is a voluntary action carried out by restraining the appetite for eating, drinking and anything that could break it for a certain period of time. One example of fasting is Ramadan fasting. Ramadan fasting is a fast that is carried out during the month of Ramadan for 29 days or 30 days. The time for fasting during Ramadan begins when the sun rises at dawn until sunset. Fasting is a voluntary action carried out by restraining the appetite for eating, drinking and anything that could break it for a certain period of time. The time for fasting during Ramadan begins when the sun rises at dawn until sunset. Fasting is a deep practice in Islam and has the potential to impact human health, especially in the context of obesity and diabetes. Aim: To determine the effect of fasting according to Islamic and scientific perspectives in reducing weight in obese and diabetic patients. Methods: This research involved a careful literature review and analysis of data from a variety of relevant sources. We evaluated scientific research on fasting in the context of weight loss and diabetes management. We also combine it with the Islamic religious view of fasting, especially during the month of Ramadan. Results: Fasting, both from an Islamic and scientific perspective, can have a positive impact on obese and diabetic patients. Ramadan fasting, which involves fasting from dawn to sunset, has been linked to improved blood sugar control and weight loss in diabetes patients. Additionally, intermittent fasting, such as the 16/8 method, has been shown to be effective in improving insulin sensitivity and reducing body weight in obese individuals. Studies also show that fasting can reduce the risk of heart disease, which is often associated with diabetes. Discussion: This article discusses health implications from two points of view: religion and science. Combining Islamic views on fasting with scientific research provides a strong basis for applying fasting methods in the management of obesity and diabetes. Conclusion: Fasting, from both an Islamic and scientific perspective, has great potential in reducing weight and managing diabetes in obese patients. This approach may be an effective adjunct in the treatment of this condition. Therefore, it is important to understand and utilize the benefits of fasting wisely, taking into account religious views and medical recommendations..